Economics and equity in the development of Open Research Europe - Johnson, Rob (Septentrio Conference Series, 2022)
Open Research Europe (ORE) is the open access peer-reviewed publishing platform offered by the European Commission as an optional service to Horizon 2020 and Horizon Europe beneficiaries at no cost to them. The platform enables researchers to publish open access without paying out of their research budgets and while complying with their open access obligations. This paper identifies potential financing and governance model(s) that would operationalize ORE as a collective publishing enterprise, supported by research funders and possibly research organizations, as of 2026. The aim of this study is to develop a sustainable, scalable funding model that is not based on article publication charges (APCs). To this end, the main business and financing models for not-for-profit publishing services were reviewed, based on a series of case studies and interviews with seven leading not-for-profit service providers. The paper outlines possible business model(s) for the financing of the operations of the Open Research Europe platform in the future and sets out actionable recommendations for implementing such a business model, appropriate to the scope and scale of the endeavour. It assesses how to incorporate equity into the design of Open Research Europe; and how to make Open Research Europe sustainable in the long run.